2004
DOI: 10.1007/s10811-004-5508-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening marine algae from China for their antitumor activities

Abstract: Thirty-nine species of marine algae collected from the coast of China were screened for their antitumor activities, and eight species Leathesia difformes, Polysiphonia urcedata, Scytosiphon lomentarius, Gloiopeliis furcata, Punctaria latifolia, Symphyocladia latiuscula, Rhodomela confervoides and Ulva pertusa showed potent cytotoxic activities. Three, Rhodomela confervoides, Scytosiphon lomentarius and Gloiopeliis furcata, were used for further investigation. More than 30 compounds were isolated and purified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
(20 reference statements)
2
35
1
Order By: Relevance
“…Studies on bioactivity of marine algae against cancer cell lines have been reported in previous researches, where the findings have brought great promise to the development of cancer treatment activities (Albano et al 1990;Berlinck et al 1996). Some studies involved general extractions of seaweeds while others applied extraction of specific metabolites such as carotene, bromophenols and carrageenan (Ly et al 2005;Xu et al 2004). In the present study, 90% methanolic extracts, 70% acetonic extracts and aqueous extracts of K. alvarezii and K. striatum were studied for their potential to inhibit the growth of HeLa cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bioactivity of marine algae against cancer cell lines have been reported in previous researches, where the findings have brought great promise to the development of cancer treatment activities (Albano et al 1990;Berlinck et al 1996). Some studies involved general extractions of seaweeds while others applied extraction of specific metabolites such as carotene, bromophenols and carrageenan (Ly et al 2005;Xu et al 2004). In the present study, 90% methanolic extracts, 70% acetonic extracts and aqueous extracts of K. alvarezii and K. striatum were studied for their potential to inhibit the growth of HeLa cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Some metabolites such as bromophenols, carotene and steroids were isolated and purified in some algae and their activity against some cancer cell lines were demonstrated (Xu et al, 2004). Also, in another study, it was shown that the sulfated compounds such as fucoidans which were extracted from Sargassum polycystum and some other brown algae exhibited important roles against some human cancer cell lines (Ly et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Marine algae have shown cytotoxic and antitumour nature [8,9]. Seaweed and their organic extracts exhibited cytotoxic activity which also showed in several literatures that highlighted the potential nature of marine products and in vitro, as well as in vivo anti-proliferative activity in human cancer cell lines [10,11].…”
Section: Introductionmentioning
confidence: 90%